Efficacy and safety of immune checkpoint inhibitors in patients with advanced non–small cell lung cancer (NSCLC): a systematic literature review. (1st January 2020) - Wagner, Gernot; Stollenwerk, Hannah Karolina; Klerings, Irma; Pecherstorfer, Martin; Gartlehner, Gerald; Singer, Josef
ABSTRACT: Background: Therapeutic strategies with immune checkpoint inhibitors (ICIs) counteract the immunosuppressive effects of programmed cell death protein-1 (PD-1) and ligand-1 (PD-L1). ICI treatment has emerged in first- and second-line therapy of non–small cell lung cancer (NSCLC). As immunotherapeutic treatment with ICIs is a dynamic field where new drugs and combinations are constantly evaluated, we conducted an up-to-date systematic review on comparative efficacy and safety in patients with advanced NSCLC. Methods: We searched PubMed up to February 2020 and Embase, CENTRAL, and clinical trial registries up to August 2018. Additionally, we checked reference lists. We dually screened titles, abstracts and, subsequently, full-texts for eligibility. Two reviewers assessed the risk of bias and graded the certainty of evidence following GRADE (Grading of Recommendations Assessment, Development and Evaluation). For second-line therapy, we performed random-effects meta-analyses. Due to considerable clinical heterogeneity, we reported first-line results narratively. Results: Of 1497 references, we identified 22 relevant publications of 16 studies. For first-line therapy, a combination of an ICI with chemotherapy improved progression-free survival and overall survival compared to chemotherapy but increased the risk of serious adverse events. Single-agent pembrolizumab increased overall and progression-free survival in patients with PD-L1 expression of ≥50% and resulted in less TRAE than chemotherapy. Compared to placebo, maintenance therapy with durvalumab increased overall and progression-free survival at the downside of higher risk of TRAE. For second-line therapy, a random-effects meta-analysis yielded a statistically significantly improved overall survival (OS) and progression-free survival (PFS) for ICIs compared to docetaxel (HR 0.69; 95% CI: 0.63–0.75 for OS; HR 0.85; 95% CI: 0.77 − 0.93 for PFS; 6 studies, 3478 patients; median OS benefit in months: 2.4 to 4.2). In meta-analysis, risk of any treatment-related adverse events of any grade was lower for ICI than docetaxel as second-line therapy (RR 0.76, 95% CI: 0.73–0.79; 6 studies, 3763 patients). Conclusion: In first-line therapy of patients with advanced NSCLC, ICI is effective when combined with chemotherapy not depending on PD-L1 expression, or as monotherapy in high PD-L1 expressing tumors. For second-line therapy, single-agent ICI improves efficacy and safety compared to docetaxel.